Numerical Simulation of Transpiration Cooling for a High-Speed Vehicle with Substructure - Dataset - Naved, I; Hermann, T; McGilvray, M (University of Oxford, 2022)
This paper presents a numericalmodel that assesses the effect of applying transpiration cooling to both the outerwall and the substructure of a high-speed flight vehicle. The porous impulse response analysis for transpiration cooling evaluation (PIRATE) code has been extended and validated to account for quasi-two-dimensional lateral heat conduction effects, thereby allowing for analysis of more complex geometries. This enables very fast calculations of the two-dimensional transient temperature response of a transpiration-cooled thermal protection system suitable for first-order systems studies. To solve for the transpiration-cooled outer wall and a two-dimensional solid substructure, PIRATE has been coupled with the commercial finite element package COMSOL. This enables modeling of the longer duration thermal effects of the integrated heat load over a flight trajectory. Transpiration cooling using helium coolant has been applied to awing leading-edge model with an aluminum substructure. Carbon–carbon ceramic composite and the ultra-high-temperature ceramic Zirconium diboride (ZrB2) are chosen as candidate materials. Results for the substructure temperature history for the space shuttle reentry trajectory are obtained, showing that transpiration cooling can lead to a 35% reduction in peak substructure temperature and a 65% reduction in thermal gradients.